SPECIFIC FEATURES OF DETECTIVE FICTION (Academicia Globe: Inderscience Research, 2024)
The genre of detective novels, with its specific features and structures, occupies a special place in literature. This genre mainly aims to entertain the reader through stories built around mysterious events, murders or crimes. The poetics of detective novels is aimed at studying the aesthetic and artistic aspects of this genre.